Fate of a coronary artery intramural haematoma complicating aortic root surgery: a case report. Issue 5 (4th September 2020) - Folino, Giulio; Scaffa, Raffaele; Salica, Andrea; De Paulis, Ruggero
Abstract: Background: Coronary intramural haematoma (CIH) is an uncommon but potentially life-threatening complication during aortic root surgery (such as Bentall procedure). Depending on its extension it can lead to cardiogenic shock. Documented reports of this complication are lacking in literature. Case summary: In the report we present a case of CIH and its management and we show a stepwise imaging of the healing process that gives an insight of the fate of CIHs. Discussion: This case raises awareness of CIH as differential diagnosis for myocardial ischaemia during aortic root surgery. It underlines the effectiveness of immediate surgical revascularization, highlights the potential temporary role of coronary artery bypass graft that can stabilize the acute coronary syndrome and may give time to the CIH to reabsorb and native coronary circulation to re-establish.